Analysis of Sexual Dimorphism in a Population of Dogs of the Romanian Mioritic Shepherd Dog Breed - Dorel Dronca; Ioan Peț; Lavinia Ștef; Gabi Dumitrescu; Liliana Ciochină Petculescu; Silvia Pătruică; Mihaela Ivancia; Eliza Simiz; Adela Marcu; Marioara Nicula; Ion Carabă; Silvia Erina; et al. (Scientific Papers Animal Science and Biotechnologies, 2023)
Romanian Mioritic Shepherd Dog was selected from a natural population breed in Carpathian Mountains of Romania. The aim of this study was to analyze the existence and size of sexual dimorphism in a population of 26 males and 23 females of the Mioritic Shepherd Dog breed, for 10 body measurements: withers height, middle back height, croup height (iliac), base of tail height (coccyx), croup width, body length, tail length, thorax depth, thorax width and thorax perimeter. The animals were registered with the Romanian Mioritic Association Club from Romania. Following the study on the significance of statistical differences between body measurements recorded in 26 males and 23 females, it was concluded that sexual dimorphism is evident in the population of the Romanian Mioritic shepherd dog studied in this paper. We recommend that dog breeders of this breed take into account the genetic improvement programs, also the results presented in this paper.